Islam dan Moral dalam keluarga dan masyarakat - Nafiah, Dafiatun (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2024)
This article examines the role of Islamic teachings in shaping moral values in the family and society. Islam as a religion that regulates all aspects of life, provides clear guidelines regarding morality, both through the Qur'an, Hadith, and the teachings of scholars. In the context of the family, Islam emphasizes the importance of a harmonious relationship between husbands, wives, parents, and children, with the principles of affection, justice, and mutual respect. In the context of society, moral values such as deliberation, please help and friendship. Islam plays an important role in building a just, safe, and prosperous society, by emphasizing social responsibility and concern for others, Through this study, it is hoped that readers can understand the depth of Islamic teachings regarding morality in forming a happy family and a moral society.